Research on evidence-based social intervention guidelines and standards Ⅲ: promote the scientific implementation of standards based on evidence-based principles - ZHU Yumeng; 2; GAI Qiongyan; CHEN Hao; ZENG Xiantao; SHI Nannan; GAO Xiangyu; BAI Zhenggang; Campbell China Network (Yixue xinzhi zazhi)
China has currently developed a large number of standards, but the overall utilization rate of standards is not high, and strengthening the practical application of standards is an urgent problem to be solved. The implementation of standards based on evidence-based principles is gradually being widely accepted. Guided by the theory of implementation science, this study specifically describes the current status of standards implementation in China, analyses international experiences such as UK's the National Institute for Health and Care Excellence (NICE), the International Organization for Standardization (ISO), and the California Evidence-Based Clearinghouse for Child Welfare (CEBC) , and discusses the specific steps and methods to promote the scientific implementation of the standards based on the evidence-based concept. The implementation was divided into four phases, "exploration - preparation - implementation-sustainment", and subdivided into different steps. In order to further promote the scientific application of standards, it is also necessary to set up standards implementation committees, adopt both voluntary and government-mandated approaches, and establish an evaluation indicator system for the implementation of standards.